Sailing through the fickle waters of food delivery platform work in Serbia - Petrović, Mila (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2023)
While it is true that food delivery platforms are a novel phenomenon, their presence was barely noticeable until the COVID-19 pandemic struck and a state of emergency was declared. This state of emergency led to various measures, including the imposition of curfews, sometimes extending for days. These restrictions on the freedom of move- ment rendered it impossible for citizens to leave their homes without special permits. Delivery couriers, equipped with the required movement permits, were seen as a lifeline by the housebound populace. Gradually, necessity evolved into habit, propelling these platforms to become some of the fastest-growing businesses in Serbia. Today, it is almost unthinkable to step outside without encountering a delivery courier from Glovo, Wolt or Mr. D. However, the rise of food delivery platform work in Serbia has not been without challenges. One significant issue is the limited protection afforded to self-em- ployed persons working for these platforms. Additionally, there is a matter of violating the rights of employees in limited liability companies that have entered into “partnership agreements” with the platforms. The problem of informal employment also looms large, often manifesting in unofficial collaborations between entrepreneur-status workers and their colleagues. Despite efforts to address these issues, Serbia has yet to establish a clear definition of what constitutes a platform worker and the rights they are entitled to. This leaves us pondering the crucial question: where do we go from here?
Keywords: delavci; delovno pravo; dostava hrane; družbe z omejeno odgovornostjo; platforme; podjetja; pravice delavcev; samozaposleni; Srbija